Positive inotropic effects of carbon monoxide-releasing molecules (CO-RMs) in the isolated perfused rat heart - Musameh, M D (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: Carbon monoxide (CO) generated by the enzyme haeme oxygenase-1 (HO-1) during the breakdown of haeme is known to mediate a number of biological effects. Here, we investigated whether CO liberated from two water soluble carbon monoxide-releasing molecules (CO-RMs) exerts inotropic effects on the myocardium. EXPERIMENTAL APPROACH: Rat isolated hearts perfused either at constant flow or constant pressure were used to test the effect of CO-RMs. KEY RESULTS: CORM-3, a fast CO releaser, produced a direct positive inotropic effect when cumulative doses (3, 10 and 30 μg min(−1)) or a single dose (5 μM) were infused at either constant coronary pressure (CCP) or constant coronary flow (CCF). The inotropic effect mediated by CORM-3 was abolished by blockade of soluble guanylate cyclase or Na(+)/H(+) exchanger, but not by inhibitors of L-type Ca(2+) channels and protein kinase C. CORM-3 also caused a slight reduction in heart rate but did not alter coronary flow. In contrast, the slow CO releaser CORM-A1 produced significant coronary vasodilatation when given at the highest concentration (30 μg min(−1)) but exerted no effect on myocardial contractility or heart rate. CONCLUSION AND IMPLICATIONS: A rapid CO release from CORM-3 exerts a direct positive inotropic effect on rat isolated perfused hearts, whereas CO slowly released by CORM-A1 had no effect on myocardial contractility but caused significant coronary vasodilatation. Both cGMP and Na(+)/H(+) exchange appear to be involved in this effect but further work is needed to determine the relative contribution of each pathway in CO-mediated inotropic effect.